Analysis of Leaf Features in Chili Plants Using Automated Color Equalization (ACE) - ., Basiroh; Kurniasih, Nuning; Asmara Jati, Dian; Zulida Situmorang, Nina; Sukrisno, Heni; ., Sujito (International Journal of Engineering and Technology, 2018)
Chili is a variety of crop groups that have promising business prospects. To obtain optimal agricultural yield, then the process of plant care and how to planting should be maximal. Constraints often experienced by farmers in the process of planting chili in Magelang regency of Indonesia is a disease of yellow leaves. Some diseases in plants can be identified using precision technology, one of them is by using an image or image-based technology. In previous studies, no one has analyzed using feature extraction using ACE as an analysis to detect plant disease in chili. In this study will extract features using Automated Color Equalization (ACE) which is then classified using SVM (Support Vector Machine) for disease identification based on its leaves. With this method, the accuracy of the extraction results in a combination of 80% texture features, color feature extraction, and a combination of 80% color feature textureÂ Â